1999
DOI: 10.1038/sj.onc.1202607
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant activation of pathways downstream of Grb2 and PI 3-kinase is required for MET-mediated metastasis

Abstract: The Met tyrosine kinase ± the HGF receptor ± induces cell transformation and metastasis when constitutively activated. Met signaling is mediated by phosphorylation of two carboxy-terminal tyrosines which act as docking sites for a number of SH2-containing molecules. These include Grb2 and p85 which couple the receptor, respectively, with Ras and PI 3-kinase. We previously showed that a Met mutant designed to obtain preferential coupling with Grb2 (Met 2xGrb2 ) is permissive for motility, increases transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 45 publications
3
52
1
Order By: Relevance
“…This provides a mechanism for Ron activation by HGF in the case of MSP de®ciency during embryonic development. The response to HGF and MSP through the activation of Met and Ron is mediated by the same pathways, mainly by Ras and by PI-3 Kinase (Wang et al, 1996;Bardelli et al, 1999). Met can regulate growth and transformation by activating the MAP kinase cascade through Grb2/Sos/Ras complex whereas the Ron pathway is directed more towards cellular movement and matrix invasion (Santoro et al, 1996;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a mechanism for Ron activation by HGF in the case of MSP de®ciency during embryonic development. The response to HGF and MSP through the activation of Met and Ron is mediated by the same pathways, mainly by Ras and by PI-3 Kinase (Wang et al, 1996;Bardelli et al, 1999). Met can regulate growth and transformation by activating the MAP kinase cascade through Grb2/Sos/Ras complex whereas the Ron pathway is directed more towards cellular movement and matrix invasion (Santoro et al, 1996;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the high levels of MET, our inducible system led to a strong decrease of both MET mRNA (Supplementary Figure 1b) and protein (Figure 2a,upper panel) in the presence of doxycycline. On MET silencing, we also observed impairment in activation of p42/44 mitogen-activated protein kinase (MAPK) and AKT, two downstream effectors of MET involved in the invasive (Grotegut et al, 2006) and anti-apoptotic response, respectively (Bardelli et al, 1999;Figure 2a).…”
Section: Met Silencing Inhibits Invasive Growth 'In Vitro'mentioning
confidence: 95%
“…The contribution of specific signals to MET activity in tumours has been partially dissected through the manipulation of the consensus sequences that mediate the recruitment of distinct transducers. By converting the multifunctional docking site of an oncogenic mutant of MET into preferential binding motifs for GRB2 or PI3K, it was demonstrated that Ras signals are primarily involved in MET-triggered cell proliferation, whereas PI3K recruitment is required for the induction of cell motility and invasion; however, a fully metastatic phenotype can be recapitulated only when both effectors are concomitantly associated with MET 137,138 . Thus, combined activation of multiple pathways is necessary to instruct the full execution of MET-dependent invasive growth in cancer cells.…”
Section: Met Signalling In Development and Diseasementioning
confidence: 99%